2022
DOI: 10.1093/ofid/ofac095
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Stenotrophomonas maltophilia Resistance for a More Rational Therapeutic Approach

Abstract: Stenotrophomonas maltophilia is an underappreciated source of morbidity and mortality among Gram-negative pathogens. Effective treatment options with acceptable toxicity profiles are limited. Phenotypic susceptibility testing via commercial automated test systems is problematic and no FDA breakpoints are approved for any of the first-line treatment options for S. maltophilia. The lack of modern pharmacokinetic/ pharmacodynamic data for many agents impedes dose optimization and the lack of robust efficacy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 125 publications
(158 reference statements)
0
21
0
Order By: Relevance
“… S. maltophilia is an extremely challenging pathogen with very limited treatment options due to its prolific intrinsic resistome ( 26 , 27 ). Although SMX-TMP has traditionally been considered the drug of choice, there are no rigorous clinical data to support its use, and the optimal therapy remains unknown ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“… S. maltophilia is an extremely challenging pathogen with very limited treatment options due to its prolific intrinsic resistome ( 26 , 27 ). Although SMX-TMP has traditionally been considered the drug of choice, there are no rigorous clinical data to support its use, and the optimal therapy remains unknown ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cefiderocol has demonstrated reliable activity against S. maltophilia isolates, including those resistant to TMP‐SMX and levofloxacin 71 . Additionally, cefiderocol possesses stability against serine and metalloenzyme β‐lactamases, conferring activity against multidrug‐resistant S. maltophilia 72 .…”
Section: Methodsmentioning
confidence: 99%
“…Cefiderocol has demonstrated reliable activity against S. maltophilia isolates, including those resistant to TMP-SMX and levofloxacin. 71 Additionally, cefiderocol possesses stability against serine and metalloenzyme β-lactamases, conferring activity against multidrug-resistant S. maltophilia. 72 CLSI set an experimental S. maltophilia susceptibility breakpoint for cefiderocol of 4 mg/L with a 2021 update shifting the susceptible breakpoint to 1 mg/L.…”
Section: Cefiderocolmentioning
confidence: 99%
“…Average susceptibility rates for this agent varies among geographical regions, being the highest in Europe (>95%), followed by the Middle East (≈93%), USA (≈90%), Latin America (≈80%), and the lowest in Asia (<80% in China; 87% in Korea) [17,31 ▪ ,34 ▪ ,42,83 ▪▪ ,84 ▪ –88 ▪ ]. SXT lacks established PK/PD index or target threshold for efficacy or toxicity, which severely impairs the ability to optimize its clinical use [34 ▪ ,89 ▪ ,90 ▪▪ ,91 ▪▪ ,92]. In fact, data supporting guidance-recommended dosing of 8–12 mg/kg/day [trimethoprim (TMP) component] is sparse [93].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given that the multidrug efflux pumps that confer resistance to SXT often confer cross-resistance to FLQs and BL/BLIs, but do not affect MIN, MIN is often utilized in the context of SXT and LVX resistance [92]. However, similarly to SXT and LVX, the in vitro or in vivo PK/PD and clinical outcomes data are scarce to determine if the in vitro susceptibility translates into clinical efficacy [89 ▪ ,110]. Initial PD studies reported that MIN achieves serum concentrations comparable to other tetracyclines, with peak serum concentrations ranging from 3 to 8.75 mg/l following i.v.…”
Section: Introductionmentioning
confidence: 99%